Kepememimpinan Musa Sebagai Pedoman Bagi Pemimpin Rohani Di Gereja Masa Kini - Adi Suhenra Sigiro (ILLUMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2023)
The growing church is determined by the quality of spiritual leaders. However, nowadays there are spiritual leaders whose ministry focus is themselves, with the aim of gaining name and popularity. Apart from that, there are spiritual leaders who leave the ministry because they feel they have no more calling to lead the congregation, there are also spiritual leaders who leave the ministry because they feel they have no more calling to lead the congregation. There are also spiritual leaders who carry out their duties and ministry in the church no longer based on Biblical leadership. Therefore, this research will explore the leadership of Moses which is a guide for spiritual leaders in the church today. The research method used is literature research. This method collects data and information in the form of documents, data archives and other literature information. The writer will do a descriptive approach. The process of analysis carried out is to use reliable sources of literature journals, books and articles such as to support the analysis of the research topic. Based on the results of the research, guided by Musa's leadership, a spiritual leader in the church today includes the following: A spiritual leader in the church must have a calling from God, have a vision that comes from God, be able to build a relationship with God, have good character. patient, humble and gentle. In addition, must be able to form a new leader.